Redes sociales como medio publicitario de emprendedores en la ciudad de Babahoyo. Diciembre 2020 - Mora León, Edinson Yoel (2021)
In the present case study, the social network Facebook was analyzed as an advertising medium for entrepreneurs in the city of Babahoyo in December 2020, whose objective was to determine the influence of the use of the social network Facebook as a tool to promote these fans page. To fulfill this purpose, the methodology applied was qualitative, through diagnostic, descriptive and exploratory research, where the technique used was direct observation, through observation sheet. The subject of this research was five local businesses, such as; Yummy Live, SuperCookie, As Stamp, Globoideas.ec and Bam-Bam Roasts. Based on the results obtained, it was found that the aforementioned businesses have generalities in terms of the communication approach, since they currently handle one-way communication, showing a lack of use in terms of the use of the functions offered by the platform, it is therefore recommended that communication and management strategies be structured, through the realization of attractive, interactive and functional content.